Characterization of Korean Male Breast Cancer Using an Online Nationwide Breast-Cancer Database: Matched-Pair Analysis of Patients With Female Breast Cancer. Issue 16 (April 2016) - Choi, Min-Young; Lee, Se Kyung; Lee, Jeong Eon; Park, Hyung Seok; Lim, Seung Taek; Jung, Yongsik; Ko, Byung Kyun; Nam, Seok Jin
Abstract : Abstract: The aim of this study is to review the characteristics and the survival rate in male breast cancer (MBC) patients in Korea over a 31-year period. Additionally, we analyzed the overall survival (OS) rate of a group of MBC matched to females with breast cancer. We retrospectively analyzed the data from 400 Korean patients who were treated for MBC from 1978 to 2009. Patient demographics and clinical information were routinely documented throughout the study period. Survival and prognostic factors were evaluated. Each MBC patient was matched with 5 female breast cancer (FBC) patients based on 7 characteristics and we compared the OS rates between the 2 groups. For MBC cases, the median follow-up was 72 months and the 5-year OS rate was 85.9%. In univariate analyses, the prognostic factors influencing OS were age (more than 60 years, P <0.001), tumor size (>2 cm, P = 0.007), and having a negative progesterone receptor (PR) status ( P = 0.042). Only the age ( P = 0.028) and tumor size ( P = 0.024) were significant prognostic factors for OS in multivariate analysis. After matching, we had 260 male patients matched to 1300 female patients for analysis. Compared with cases among females, the rate of mastectomy was higher among MBC cases and tumors, which were almost invasive ductal carcinomas (IDCs), were more likely to be located in the central part of the breast. For MBC cases, the percentage of adjuvant radiation therapy was low compared with female cases. The primary hormone therapy agent used was tamoxifen. The 5-year OS rates were similar in MBC compared with FBC (91.0% vs. 92.6%, P = 0.300). We found that only the age (more than 60 years) and tumor size were independent prognostic factors of survival in MBC. The prognosis for MBC is similar to that for FBC given similar stage and hormone-receptor status.